A Novel in Vivo Model for Assessing the Impact of Geophagic Earth on Iron Status - Seim, Gretchen L. (Nutrients, 2016)
The causes and consequences of geophagy, the craving and consumption of earth, remain enigmatic, despite its recognition as a behavior with public health implications. Iron deficiency has been proposed as both a cause and consequence of geophagy, but methodological limitations have precluded a decisive investigation into this relationship. Here we present a novel in vivo model for assessing the impact of geophagic earth on iron status: Gallus gallus (broiler chicken). For four weeks, animals were gavaged daily with varying dosages of geophagic material or pure clay mineral. Differences in haemoglobin (Hb) across treatment groups were assessed weekly and differences in liver ferritin, liver iron, and gene expression of the iron transporters divalent metal transporter 1 (DMT1), duodenal cytochrome B (DcytB) and ferroportin were assessed at the end of the study. Minimal impact on iron status indicators was observed in all non-control groups, suggesting dosing of geophagic materials may need refining in future studies. However, this model shows clear advantages over prior methods used both in vitro and in humans, and represents an important step in explaining the public health impact of geophagy on iron status.